Germinative potential of ‘Pata-de-Vaca’ seeds at different maturation stages under various temperatures - Guariz,Hugo Roldi (2022)
Abstract Bauhinia monandra Kurz has ornamental characteristics as the shape of its crown and the exuberance of its flowering, being and is widely cultivated in urban afforestation in Brazilian regions. The production of forest seedlings is essential not only to meet the demand of urban afforestation, but also to conserve forests. However, studies on B. monandra regarding the degree of fruit maturity on seed performance are scarce. Thus, the objective of the current work was to verify the germination potential of B. monandra seeds at different stages of maturation at five constant temperatures. The germination percentage, germination speed index (GSI), mean germination time (t), relative germination frequency, and mean germination speed (MGS) were evaluated. Initially, the mature seeds had a water content of 8.5% and the immature seeds of 68.3%. Mature seeds reached high germination percentages, above 96% for temperatures of 25, 30, and 35 ºC. The immature seeds demonstrated low germination percentages, reaching the highest percentage of 33% for the temperature of 25 ºC, followed by the temperatures of 30 ºC and 35 ºC, with respective percentages of 32% and 20%. Mature seeds demonstrated the highest GSI value (11.79) for the estimated temperature of 26.94 ºC and immature seeds the highest value of t (7.85) for the temperature of 26.56 ºC. It is concluded that mature seeds aggregate higher germination at an estimated temperature of 24.72 ºC and that immature seeds present unsatisfactory germination performance.